2013
DOI: 10.1093/jxb/ert247
|View full text |Cite
|
Sign up to set email alerts
|

Uncorrelated evolution of leaf and petal venation patterns across the angiosperm phylogeny

Abstract: Early angiosperm evolution, beginning approximately 140 million years ago, saw many innovations that enabled flowering plants to alter ecosystems globally. These included the development of novel, flower-based pollinator attraction mechanisms and the development of increased water transport capacity in stems and leaves. Vein length per area (VLA) of leaves increased nearly threefold in the first 30-40 million years of angiosperm evolution, increasing the capacity for transpiration and photosynthesis. In contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 60 publications
4
52
2
Order By: Relevance
“…Other traits similarly varied approximately two orders of magnitude (Figs & ). VLA exhibited a similar range to that seen by Roddy et al (), ranging from 0.21 mm mm −2 for Agapanthus africanus to 12.02 for Calycanthus occidentalis . Within clades, VLA ranged for the basal angiosperms (magnoliids and Illicium ) from 2.96 mm mm −2 for Liriodendron tulipifera to 12.02 mm mm −2 for Calycanthus occidentalis , for the monocots from 0.21 mm mm −2 for Agapanthus africanus to 1.65 mm mm −2 for Iris douglasiana , and for the eudicots from 1.12 mm mm −2 for Rhododendron sp.…”
Section: Resultssupporting
confidence: 83%
“…Other traits similarly varied approximately two orders of magnitude (Figs & ). VLA exhibited a similar range to that seen by Roddy et al (), ranging from 0.21 mm mm −2 for Agapanthus africanus to 12.02 for Calycanthus occidentalis . Within clades, VLA ranged for the basal angiosperms (magnoliids and Illicium ) from 2.96 mm mm −2 for Liriodendron tulipifera to 12.02 mm mm −2 for Calycanthus occidentalis , for the monocots from 0.21 mm mm −2 for Agapanthus africanus to 1.65 mm mm −2 for Iris douglasiana , and for the eudicots from 1.12 mm mm −2 for Rhododendron sp.…”
Section: Resultssupporting
confidence: 83%
“…For Arabidopsis thaliana , quantitative trait loci mapping of leaf- and flower-size traits has not revealed any correlations between those trait categories (Juenger et al, 2005). Furthermore, Roddy et al (2013) found no proof of correlated evolution for leaf and petal venation patterns across the angiosperm phylogeny. Those earlier results, as well as our data, suggest that the physiological traits of leaves and flowers may arise from non-correlated selection pressures and functions.…”
Section: Discussionmentioning
confidence: 89%
“…In fact, the “leaf economic spectrum” occurs across all major terrestrial plant groups, where a higher (LMA) is invested in longer-lived leaves (Wright et al, 2004; Sack et al, 2013; John et al, 2017). The role of water transport traits in flower evolution is complex, with phylogeny an important determinant of flower hydraulic characteristics (e.g., vein density) that has evolved independently of leaves (Roddy et al, 2013). In addition, the benefits associated with longevity are also very different in flowers when compared to leaves.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies of K flower and other hydraulic traits (Roddy et al, ; Roddy, Brodersen, & Dawson, ), flowers of the genus Calycanthus (Calycanthaceae; Zhou, Renner, & Wen, ) consistently had traits associated with high rates of water supply via the xylem (i.e., high vein length per area), high water loss (minimum epidermal conductance; g min ), and high hydraulic conductance ( K flower ). These extreme trait values, particularly for Calycanthus occidentalis , suggest that these flowers can transport substantial amounts of water, possibly even outpacing leaf transpiration.…”
Section: Introductionmentioning
confidence: 93%